Virginia Woolf and the Bloomsbury avant-garde : war, civilization, modernity - Froula, Christine, 1950- (Gender and culture., 2005)
Virginia Woolf and the Bloomsbury Avant-Garde traces the dynamic emergence of Woolf's art and thought against Bloomsbury's public thinking about Europe's future in a period marked by two world wars and rising threats of totalitarianism. Educated informally in her father's library and in Bloomsbury's London extension of Cambridge, Virginia Woolf came of age in the prewar decades, when progressive political and social movements gave hope that Europe ""might really be on the brink of becoming civilized, "" as Leonard Woolf put it. For pacifist Bloomsbury, heir to Europe's unfinishe